Music Therapy Alleviates Motor Dysfunction in Rats With Focal Cerebral Ischemia–Reperfusion Injury by Regulating BDNF Expression - Chen, Weiguan; Zheng, Jiaxuan; Shen, Guangyu; Ji, Xin; Sun, Linlin; Li, Xia; Xu, Feng; Gu, Jin-hua (Frontiers in Neurology, 2021)
Background/Aim: Music-based therapy plays a role in central nervous system diseases. We aimed to explore the effect of different doses and durations of music therapy on motor function recovery after stroke and the underlying molecular mechanisms. Methods: Adult male Sprague–Dawley rats were subjected to middle cerebral artery occlusion (MCAO) for 1 h, which was followed by reperfusion. In experiment 1, the rats that survived 1 week after MCAO surgery were randomly allocated into four groups (n = 10 per group): MCAO group, 1 h music group (Mozart K.448 music therapy 1 h per day for 2 weeks), 12 h music group (Mozart K.448 music therapy 12 h/day for 2 weeks), and accelerated music group (reversely accelerated music therapy 12 h for 2 weeks, AM group). In experiment 2, the survived rats were randomly divied into three groups: MCAO group, 12 h music group (music therapy 12 h/day for 3 weeks), and 12 h music-R group (music therapy 12 h/day for 2 weeks and rest for 1 week). Three neuroscores were evaluated daily, starting on the first day after surgery until the end of the experiment. The rats were killed 3 weeks after MCAO surgery in experiment 1 or 4 weeks after surgery in experiment 2. Nissl staining of infart core, peri-infarct zone, and motor cortex was performed to assess neuronal survival and regeneration. Western blot and immunofluorescence were used to detect the expression and distribution of brain-derived neurotrophic factor (BDNF) and glial fibrillary acidic protein (GFAP) in ipsilateral hemispheres. Results: In the experiment of different music therapy doses, the motor function in the 12-h music group but not in the 1-h music group and AM group was significantly improved compared with that of the MCAO group. The BDNF protein level of the ipsilateral hemisphere motor cortex in the 12-h music group and the 1-h music group was higher than that of the MCAO group. The neurons and Nissl bodies were more in the 12-h music group than in the MCAO group. Immunofluorescence assay showed that a 12 h music therapy induces BDNF and GFAP accumulation at the damage boundary. In the experiment of different music therapy durations, 3 weeks music therapy (12 h music group) induced more longer cell synapses and more clearer cell-to-cell connections than 2 weeks music intervention (12 h music-R group). Moreover, the GFAP morphology in the 12-h music group was more similar to mature activated astrocytes than that in the 12-h music-R group. Conclusions: Music therapy may improve poststroke motor function and promote neuronal repair in the long term. The mechanism may be through stimulating BDNF and GFAP secretion in the injured motor cortex.